The Role of Employee Training and Development in Supporting Sustainable Economic Growth in Indonesia: Literature Review - Jurnalita, Aisyah Chusnul; Nisa, Nadia Fakhrun; Darmastuti, Ismi (LifeSciFi, 2024)
This article reviews the role of employee training and development in supporting sustainable economic growth in Indonesia through relevant literature analysis. Employee training and development are seen as crucial factors driving productivity, innovation, and corporate competitiveness, ultimately contributing to national economic growth. The article explores how skill development, technical capacity enhancement, and leadership training across various sectors can improve workforce effectiveness and promote the adoption of more environmentally-friendly work practices. However, challenges such as lack of infrastructure support and skill gaps still hinder the implementation of effective training programs in Indonesia. Findings from this review indicate that with appropriate investment in employee training and development, companies can create an adaptive and innovative workforce that not only supports economic objectives but also contributes to environmental sustainability. The article concludes that human resource development through employee training is key to achieving inclusive and sustainable economic growth in Indonesia.